Suicide by self-immolation in southern Iran: an epidemiological study - Ali Akbar Mohammadi; Mohammadreza Karoobi; Amirhossein Erfani; Reza Shahriarirad; Keivan Ranjbar; Mitra Zardosht; Mahboobeh-Sadat Modarresi; Zari Afrasiabi (BMC, 2020)
Abstract Background Self-immolation, as a method of suicide, is one of the most violent and extreme ways which is usually attempted by the ignition of inflammable materials, with more than 70% fatality rate. In the literature, Iran has been reported to have a high rate of self-immolation; therefore, this study aimed to evaluate the prevalence and epidemiological features of self-immolated patients. Methods In this retrospective cross-sectional multicenter study, data from burn patients from 2007 till 2017 due to self-immolation and suicide were enrolled in our study. Results Based on our data, 657 out of 3530 burn patients (18.6%) with a mean age of 31.15 (SD = 0.452) were documented as suicidal attempts; the majority were female (63.2%) and married (66.3%). Most of the patients were from rural areas (58.3%) with an education level of under diploma (63.2%). Of the patients in our study, 22 (8.7%) had comorbid systemic diseases and 115 (50.5%) had psychiatric disorders. Conclusion Due to the high prevalence of suicide by self-immolation among the Iranian population, further studies to evaluate the risk factors and clarify the high-risk group for more targeted approaches are recommended.